CREATIVE THINKING SKILL AS AN IMPORTANT ASPECT IN DISRUPTIVE ERA - Tri Yuda Bekti Pamungkas; Restu Peni Winahyu (Universitas Sebelas Maret, 2018)
Disruptive era is a change of achievement towards a better innovation. Education is one of priority to prepare human resources to confront the disruptive era. As educational actor, student must have an important think one of that is creative thinking skill. Creative thinking skill is the basis for progress of quality and the mentality of the student. Creative thinking is the way to prepare disruptive era as the complexity of competitive. As the effective execution, creative thinking will increase the cognitive processes, held to depend on the strategies employed in process execution and the knowledge being used in problem solving. This paper uses the method of theory study. It so we make a result by some of the theory and made conclusion about the important creative thinking skill in disruptive era. Creative thinking skill is the one of the main stimulus to create gold era on 2045.